Health Behaviors Before and After the Implementation of a Health Community Organization: Gangwon's Health-Plus Community Program - Joon-Hyeong Kim; Nam-Jun Kim; Soo-Hyeong Kim; Woong-Sub Park (Korean Society for Preventive Medicine, 2023)
Objectives Community organization is a resident-led movement aimed at creating fundamental social changes in the community by resolving its problems through the organized power of its residents. This study evaluated the effectiveness of health community organization (HCO), Gangwon's Health-Plus community program, implemented from 2013 to 2019 on residents' health behaviors. Methods This study had a before-and-after design using 2011-2019 Korea Community Health Survey data. To compare the 3-year periods before and after HCO implementation, the study targeted areas where the HCO had been implemented for 4 years or longer. Therefore, a total of 4512 individuals from 11 areas with HCO start years from 2013 to 2016 were included. Complex sample multi-logistic regression analysis adjusting for demographic characteristics (sex, age, residential area, income level, education level, and HCO start year) was conducted. Results HCO implementation was associated with decreased current smoking (adjusted odds ratio [aOR], 0.73; 95% confidence interval [CI], 0.57 to 0.95) and subjective stress recognition (aOR, 0.79; 95% CI, 0.64 to 0.97). Additionally, the HCO was associated with increased walking exercise practice (aOR, 1.39; 95% CI, 1.13 to 1.71), and attempts to control weight (aOR, 1.36; 95% CI, 1.12 to 1.64). No significant negative changes were observed in other health behavior variables. Conclusions The HCO seems to have contributed to improving community health indicators. In the future, a follow-up study that analyzes only the effectiveness of the HCO through structured quasi-experimental studies will be needed.